Cognitive impairment in relapsing remitting multiple sclerosis patients [Atak ve Remisyonla Giden Multipl Sklerozlu Olgularda Bilişsel İşlev Bozuklukları] - (:unkn) unknown (Ege University Press, 2012)
The purpose of this study is to evaluate the cognitive functions in cases with relapsing remitting MS during the period in which the physical disability is seen in a lower level, as well as to examine the level and predominant domain of cognitive loss while relating it with the duration of the disease, degree of disability, and number of the episodes. Materials and Methods: Twenty five (25) patients with relapsing remitting MS were included in the study.Neuropsychological test battery which is used for the assessment of cognitive functions included tests for verbal and visual memory, simple attention and sustained attention, executive functions, visuospatial ability and language. The results were compared with 17 healthy controls matched for age, gender and education level. Results: When the patient and control groups were compared, a significant impairment was observed in MS patients on short and long time free recall and clue recall, recognition processes, recent memory and free recall processes, attention and ability to maintain attention, verbal fluency and categoric fluency during memory tests, while impairment was detected in frontal functions such as difficulty in response inhibition, perseverations in Luria drawings. Conclusion: Cognitive impairment affects the quality of life independent from disability scores, and highly informative during follow-ups as it indicates the progression of the disease. Therefore, cognitive assessment should be included in routine follow-ups. Further studies are warranted to improve the definition of the limits of cognitive impairment, to highlight the physiopathogenic mechanisms and to develop treatment principles in MS.
Keywords: Cognitive impairment; Executive functions; Memory; Multiple sclerosis